La postura de la Unión Europea frente al separatismo en Cataluña - A. V. Makarycheva (Ибероамериканские тетради)
Secessionist sentiments are more common for the European Union than for other world regions. This tendency takes place to a large extent because of a crisis in the European values and religious traditions, and new priorities. Catalonia, as well as the Basque Country, tries to hold a direct dialogue with Brussels bypassing Madrid, which is accompanied with numerous difficulties: a discontent and warnings on the part of the official government of Spain, the necessity for the European Union to take into consideration the position of its member-state and many others. Despite the fact that regions started to play a more significant role in the European Union agenda, it still continues to follow the policy of a cautious attitude towards the autonomy separatism. Moreover, the EU tries to limit capabilities of the further existence and development of autonomies as independent states by institutional means. In addition, after the separation, a state is not yet a member of the European Union – it has to create new currency, it faces some economic problems. Given all these factors, autonomies will think twice before organizing a referendum, which is also difficult to hold, because it contradicts the Constitution of Spain.